Nephrometry scores: a validation of three systems for peri‐operative outcomes in retroperitoneal robot‐assisted partial nephrectomy. (5th April 2021) - Crockett, Matthew G.; Giona, Simone; Whiting, Danielle; Whitehurst, Lily; Agag, Ayman; Malki, Manar; Hussain, Muddassar; Barber, Neil J.
Abstract : Objective: To externally validate the RENAL, PADUA and SPARE nephrometry scoring systems for use in retroperitoneal robot‐assisted partial nephrectomy (RAPN). Materials and Methods: Nephrometry scores were calculated for 322 consecutive patients receiving retroperitoneal RAPN at a tertiary referral centre from 2017. Patients with multiple tumours were excluded. Scores were correlated with peri‐operative outcomes, including the trifecta (warm ischaemia time <25 min, no peri‐operative complications and a negative surgical margin), both as continuous and categorical variables. Comparisons were performed using Spearman correlation and ability to predict the trifecta was assessed using binomial logistical regression. Results: All three scoring systems correlated significantly with the main variables (operating time, warm ischaemia time and estimated blood loss), both as continuous and categorical variables. Only PADUA and SPARE were able to predict achievement of the trifecta (PADUA area under the curve [AUC] 0.623, 95% confidence interval [CI] 0.559–0.668; SPARE AUC 0.612, 95% CI 0.548–0.677). Conclusion: This study validates the RENAL, PADUA and SPARE scoring systems to predict key intra‐operative outcomes in retroperitoneal RAPN. Only PADUA and SPARE were able to predict achievement of the trifecta. As a simplified version of the PADUA scoring system with comparable outcomes, we recommend using the SPARE system.